Determinación de los factores críticos de éxito para la implementación de BPM: estudio de caso para la cadena de suministro para una empresa del sector floricultor (2017)
Business Process Management, BPM, has proven to be a tool that leads to performance and business competitiveness improvement and the supply chain processes are not alien to these advances. The purpose of this work is to identify the critical success factors, CSFs, that allow to implement BPM in the supply chain of a company in the floriculture sector. For this, a model is designed which shows the interaction between CSFs and supply chain processes through each stages of BPM adoption. A study case approach is developed in a flower crop located at the Sabana de Bogotá to validate the model empirically. We found that the experts guide was very important and so valuable, in the sense that are taken into account CSFs characteristic of Colombian companies, likewise, a method for its validation. The results of the application of the model proposed shows that the CSFs are not the same in all BPM adoption stages nor for all supply chain processes. Clearly identify the CSFs, provides a holistic vision about the supply chain processes facilitating the development of BPM projects.